Design and Development of a Micro-Curriculum for Environmental Character Education in Early Childhood Education - Megandarisari, Megandarisari; Ali, Mohammad; Hernawan, Asep Herry (Jurnal Pendidikan Progresif, 2025)
Design and Development of a Micro-Curriculum for Environmental Character Education in Early Childhood Education. Objective: This study aims to design a micro curriculum for environmental character education at the early childhood education (ECE) level that aligns with the Sustainable Development Goals (SDGs). The curriculum is designed to instill environmental awareness values in children from an early age, laying a foundation for preparing future generations. Methods: The research adopts the Design and Development (D&D) method. A needs analysis was conducted using Likert-scale questionnaires administered to 18 principals and 85 teachers from public kindergartens in Banten Province. The goal was to identify the actual conditions of environmental character education implementation and determine the essential competencies required for designing the micro curriculum. Findings: The analysis results showed no significant differences between the factual conditions in highland and lowland areas. Additionally, quantitative analysis using SPSS indicated that teachers' perceptions regarding the necessary competencies were relatively homogeneous. Based on these findings, three main topics were selected as core content for the curriculum: sustainable lifestyle, animals, and plants. The curriculum content was designed, including learning objectives, instructional materials, teaching media, learning strategies, and assessment methods. The developed micro curriculum for environmental character education was subsequently evaluated by experts in early childhood education, kindergarten principals, and kindergarten teachers to assess its feasibility. The validation results demonstrated that the curriculum was considered feasible and appropriate for implementation. Conclusion: The study concludes that public kindergartens in Banten Province require a systematic and structured curriculum for environmental character education. Moreover, the designed curriculum aligns well with the identified competency needs and has been validated as feasible based on expert and practitioner evaluations in the field of early childhood education. Keywords: curriculum development, character education, environmental awareness, early childhood education.